A85 EFFICACY AND SAFETY OF DOSE ADJUSTMENT AND DELAYED RESPONSE TO USTEKINUMAB IN MODERATE–SEVERE CROHN'S DISEASE: RESULTS FROM THE IM-UNITI MAINTENANCE STUDY. (1st March 2018) - Sands, B E; Gasink, C; Jacobstein, D; Gao, L; Johanns, J; Szapary, P; Colombel, J F; Targan, S; Ghosh, S; Sandborn, W
Abstract: Aims: Ustekinumab (UST) has been shown to induce and maintain clinical response and remission in moderate-severe Crohn's disease (CD) in 2 induction (UNITI-1 & 2) and 1 maintenance (IM-UNITI) randomized, PBO-controlled Phase 3 trials. We evaluated the efficacy of UST in 2 additional groups in IM-UNITI: patients (pts) who dose adjusted following loss of response (LOR) and pts who did not have a clinical response to IV UST during induction and had an additional subcutaneous (SC) dose. Methods: Pts in clinical response [CR-100] (≥ 100 point decrease in CDAI) after single dose IV dose were randomized to SC PBO, UST 90mg q12w or q8w. Pts who met LOR criteria, defined as a CDAI score of ≥ 220 and a ≥ 100 point increase from the IM-UNITI baseline CDAI score, between wks8 and 32 of IM-UNITI could undergo a single dose adjustment as follows: PBO→q8w, q12w→q8w, and q8w→q8w (no adjustment) and were assessed for CR-100 and clinical remission (CDAI < 150) 16wks later. Separately, UST IV non-responders received SC UST 90mg, then continued SC UST 90mg q8w if in CR 8wks later. Results: 51 (39%), 29 (23%), and 28 (22%) pts in the PBO, q12w and q8w groups, respectively, underwent dose adjustment after meeting LOR criteria. Among these pts, clinical remission and CR-100 were observed in 39% and 71% of pts adjusting PBO→q8w (a situation similar to a drug holiday), 41% and 55% in the q12w→q8w group, and 32% and 46% in the q8w→q8w group when assessed 16wks later (Table 1). Median change in CDAI after adjustment was -121, -141 and -78.5 in the PBO→q8w, q12w→q8w and q8w→q8w groups, respectively. Of 467 pts not in response to UST following IV induction in UNITI1&2, 50.5% and 28.9% were in clinical response and remission 8wks after one additional UST dose (90mg SC). Among the 251 of these pts continuing dosing at wk8 of maintenance, 68.1% were in CR-100 and 50.2% were in remission at wk44. No increases or changes in patterns of adverse events were seen among pts who dose adjusted. Conclusions: In pts who met LOR criteria, dose adjustment from UST 90mg q12w to 90mg q8w provided some additional clinical benefit compared to pts who remained on UST 90mg q8w. Additionally, pts who were initial induction non-responders can benefit from continued treatment with at least 1 SC UST dose 8wks after IV induction. Funding Agencies: Janssen Research & Development, LLC